Production of Bio-Polyurethane Foam from Pumpkin Seeds - Akanbi, Magdalene Nkeiru; Eze, Patricia Nnebuogo; Okore, Glory Jerry; Aharanwa, Bibiana Chimezie; Anyanwu, Placid Ikechukwu (Faculty of Natural and Applied Sciences Journal of Applied Biological Sciences, 2025)
Bio-based polyurethane (PU) foams were synthesized from pumpkin seed oil (PSO) polyol, extracted via the cold bulk method, converted to polyol, and blended with Arcol 1180 (petroleum-based polyol) at 30:70 and 50:50 ratios, alongside formulations containing 100% PSO polyol and 100% Arcol polyol. The physical properties of the foams, including compression set (CS), apparent density, tensile properties (such as yield strength, ultimate tensile strength, elongation at break, and Young's modulus), and porosity index, were thoroughly characterized. The surface properties and structure of the samples were studied using scanning electron microscopy (SEM), while the chemical structure was analyzed using Fourier Transform Infrared (FTIR) spectroscopy. The compression set results showed that increasing the PSO content improved compression strength, with the 50:50 PSO-PU blend exhibiting the lowest compression set (CS) value of 37.5%, followed by the 30:70 PSO-PU blend with a CS value of 44.23%, and the 100% Arcol-PU sample had the highest CS value of 49.9%. Apparent density values ranked as 30:70 PSO-PU (63.10 kg/m³) > 50:50 PSO-PU (62.0 kg/m³) > 100% Arcol-PU (27.10 kg/m³). Tensile testing showed 50:50 PSO-PU (1.80 N/mm² tensile strength; 1.36 N/mm² yield strength) outperforming 30:70 PSO-PU (1.70 N/mm²; 1.30 N/mm²), while 100% Arcol-PU exhibited the highest tensile and yield strengths (2.73 N/mm²; 2.27 N/mm²). Elongation at break was highest in 50:50 PSO-PU (5.51 mm) compared to 3.51 mm (30:70 PSO-PU) and 3.90 mm (100% Arcol-PU). Porosity indices were 43% (50:50 PSO-PU), 35% (30:70 PSO-PU), and 50% (100% Arcol-PU). SEM analysis revealed uniform, thin-walled cells in PSO-PU blends (30:70 and 50:50), but coarse, thick-walled cells in the pure PU samples (100% PSO-PU and 100% Arcol-PU). FTIR spectra confirmed the absence of free –OH groups, indicating complete conversion of hydroxyl functionalities into urethane linkages (NH–C(O)–O).